The pathway of cell dismantling during programmed cell death in lace plant (Aponogeton madagascariensis) leaves - Wertman, Jaime (BioMed Central, 2012)
BACKGROUND: Developmentally regulated programmed cell death (PCD) is the controlled death of cells that occurs throughout the life cycle of both plants and animals. The lace plant (Aponogeton madagascariensis) forms perforations between longitudinal and transverse veins in spaces known as areoles, via developmental PCD; cell death begins in the center of these areoles and develops towards the margin, creating a gradient of PCD. This gradient was examined using both long- and short-term live cell imaging, in addition to histochemical staining, in order to establish the order of cellular events that occur during PCD. RESULTS: The first visible change observed was the reduction in anthocyanin pigmentation, followed by initial chloroplast changes and the bundling of actin microfilaments. At this stage, an increased number of transvacuolar strands (TVS) was evident. Perhaps concurrently with this, increased numbers of vesicles, small mitochondrial aggregates, and perinuclear accumulation of both chloroplasts and mitochondria were observed. The invagination of the tonoplast membrane and the presence of vesicles, both containing organelle materials, suggested evidence for both micro- and macro-autophagy, respectively. Mitochondrial aggregates, as well as individual chloroplasts were subsequently seen undergoing Brownian motion in the vacuole. Following these changes, fragmentation of nuclear DNA, breakdown of actin microfilaments and early cell wall changes were detected. The vacuole then swelled, causing nuclear displacement towards the plasma membrane (PM) and tonoplast rupture followed closely, indicating mega-autophagy. Subsequent to tonoplast rupture, cessation of Brownian motion occurred, as well as the loss of mitochondrial membrane potential (ΔΨ(m)), nuclear shrinkage and PM collapse. Timing from tonoplast rupture to PM collapse was approximately 20 minutes. The entire process from initial chlorophyll reduction to PM collapse took approximately 48 hours. Approximately six hours following PM collapse, cell wall disappearance began and was nearly complete within 24 hours. CONCLUSION: Results showed that a consistent sequence of events occurred during the remodelling of lace plant leaves, which provides an excellent system to study developmental PCD in vivo. These findings can be used to compare and contrast with other developmental PCD examples in plants.